Manajemen Program Arabic Culture Dalam Menciptakan Bi’ah Arabiyah Di Perguruan Tinggi Islam. - Jazilah, Ela; Mufidah, Nuril (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2024)
This research aims to describe the management of the Arabic Culture Program run by an Islamic university in Indonesia, UIN KHAS Jember. This university has succeeded in developing an Arabic Culture program which can create an Arabic language environment (bi'ah Arabiyah), thus producing a generation of achievers in the field of Arabic. The research focuses on exploring planning and implementation activities and looking for supporting and inhibiting factors in implementing the program. The research uses a descriptive qualitative type, with data collection techniques using observation and interviews. In-depth interviews were conducted with the President of International Culture and Islamic Studies (ICIS), the head of the Arabic language division, tutors and program participants. Using Miles and Huberman data analysis, the results of the research show that: program planning is carried out through reviewing division goals and organizational mottos. Next, classes are grouped according to the level of Arabic language skills. 2) This program is implemented for 1 year with 2 meetings in 1 week with peer tutors who have better abilities than other friends, using material according to ability, based on strategies levels and direct methods as well as collaborative systems. 3) Supporting factors for program effectiveness come from tutor competence, shared goals of program participants and support from leaders. Meanwhile, obstacles come from the low commitment of tutors and participants, limited infrastructure (learning places), and the heterogeneity of program participant backgrounds. Practically, these findings provide an overview that can be adopted by other educational institutions to improve students' Arabic language skills through comprehensive planning, collaborative implementation, and systematic evaluation.